Genetic fidelity assessment of tissue culturederived Neolamarckia cadamba plantlets using DNA-based markers - Mok, Pei-Kieng; Ho, Wei-Seng (Penerbit Universiti Kebangsaan Malaysia, 2019)
Neolamarckia cadamba is one of the fast-growing tree species selected for industrial tree plantations (ITPs). As demand and supply of true-to-type planting material are increasing, micropropagation of elite N. cadamba planting material is required for the sustainable development of ITPs. However, somaclonal variation among tissue culture-derived plantlets is a bottleneck in micropropagation. The present study described the genetic fidelity of in vitro regenerated N. cadamba plantlets from first, second, third and sixth subcultures. These plantlets were obtained from axillary shoot multiplication and repeated subcultures of microshoots with three weeks interval period, which initially developed from nodal explants. By using five random amplified length polymorphism (RAPD) and two inter-simple sequence repeats (ISSR) primers, a total of 9,334 bands and 2,760 bands were amplified respectively, from a total number of 164 tested plantlets. The banding profiles for each primer was highly uniform, and the DNA bands were monomorphic across all tissue culture-derived plantlets from every four subcultures compared to the stock plants. A target gene-specific marker was also employed to detect single nucleotide polymorphism (SNP) within the targeted genomic sequence of Susy gene. There was no SNP detected from all the analysed plantlets. The current findings ascertained the efficiency and reliability of the N. cadamba micropropagation protocol at least up to six subculture cycles for mass production of true-to-type plantlets.